2023
DOI: 10.3389/fimmu.2023.1094326
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia parkeri hijacks tick hemocytes to manipulate cellular and humoral transcriptional responses

Abstract: IntroductionBlood-feeding arthropods rely on robust cellular and humoral immunity to control pathogen invasion and replication. Tick hemocytes produce factors that can facilitate or suppress microbial infection and pathogenesis. Despite the importance of hemocytes in regulating microbial infection, understanding of their basic biology and molecular mechanisms remains limited.MethodsHere we combined histomorphology and functional analysis to identify five distinct phagocytic and non-phagocytic hemocyte populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(59 citation statements)
references
References 124 publications
4
55
0
Order By: Relevance
“…Bulk RNA-seq of hemocytes originating from the tick Amblyomma maculatum showed differential expression of hemocytin and astakine during infection with the intracellular bacterium Rickettsia parkeri ( 31 ). Our scRNA-seq revealed downregulation of hemocytin and astakine expression during A. phagocytophilum and B. burgdorferi infection (Figure 3D, Supplementary Dataset 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk RNA-seq of hemocytes originating from the tick Amblyomma maculatum showed differential expression of hemocytin and astakine during infection with the intracellular bacterium Rickettsia parkeri ( 31 ). Our scRNA-seq revealed downregulation of hemocytin and astakine expression during A. phagocytophilum and B. burgdorferi infection (Figure 3D, Supplementary Dataset 9).…”
Section: Resultsmentioning
confidence: 99%
“…We observed an increased expression of genes and expansion of hemocyte subtypes involved in metabolism, cell proliferation and development following a blood meal (Figures 1-2), suggesting participation of these immune cells in the feeding or molting process. To investigate this observation, we manipulated hemocyte numbers in I. scapularis using clodronate liposomes (CLD), which have been used to deplete phagocytic hemocytes in flies, mosquitoes and, more recently, ticks ( 31, 36, 37 ). We found that the CLD treatment reduced the total number of hemocytes in nymphs (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Three independent cohorts of adult female lone star ticks ( Amblyomma americanum) representing unfed, blood-fed, and Ehrlichia -infected (Arkansas strain) ticks were prepared for hemolymph collection. Hemolymph was collected from these three cohorts using our published method with slight modifications (Adegoke et al, 2023). Collected hemolymph was resuspended in Leibovitz’s L-15 Medium supplemented with 50% BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Hemocyte mediates several immune processes ranging from phagocytosis, nodulation, melanization, and the release of antimicrobial peptides (Feitosa et Tick hemocytes exhibit remarkable heterogeneity and complexity, comprising multiple distinct subpopulations with unique functional attributes. Traditional microscopy approaches have provided valuable insights into the overall composition and morphology of tick hemocytes (Binnington and Obenchain, 1982;Adegoke et al, 2023), leading to the identification of five types: prohemocytes, plasmatocytes, granulocytes, spherulocytes, and oenocytoids (Binnington and Obenchain, 1982;Adegoke et al, 2023). Interestingly, several studies have reported fewer hemocyte types in other tick species (Sonenshine and Roe, 2013;Borovičková and Hypša, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation